Smart Digitalpreneur: Pemberdayaan UMKM melalui Pemanfaatan AI Generatif untuk Pengembangan Konten, Branding, dan Pemasaran Digital di Kecamatan Boja (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
The use of Generative Artificial Intelligence (GenAI) provides opportunities for MSMEs to improve content creativity, branding, and digital marketing. However, limited digital literacy and skills remain major challenges. This community engagement program aimed to improve the ability of MSME actors in Boja District to utilize GenAI for marketing activities. The program employed needs identification, training, hands-on practice, and mentoring. Participants were trained to use GenAI to develop prompts, promotional captions, content ideas, taglines, and content plans. The results indicated improved participants’ knowledge and skills in utilizing GenAI for content development, branding, and digital marketing. The program also encouraged the emergence of potential local digital champions who can share knowledge with other MSME actors. Therefore, integrating GenAI literacy, content development, branding, and digital marketing through practical training and mentoring can serve as an effective empowerment strategy for MSMEs in the digital transformation era.